Expansion hydroélectrique et contrôle de l’eau par l’État au Brésil (1930-1990) - Nathalia Capellini (Caravelle)
This article deals with the expansion of the Brazilian State's role in the electricity sector between 1930 and the late 1980s. Furthermore, it analyzes the controversies linked to the construction of the Tucuruí and Sobradinho hydroelectric dams. Adopting an environmental history approach, it questions the logics and political motives of this growing State involvement, revealing the links between development projects, water management and the modification of nature in the country.